FACTORS AFFECTING ON ANXIETY AMONG HYPERTENSION PATIENTS AT M.Th.Djaman GENERAL HOSPITAL SANGGAU DISTRICT, WEST BORNEO 2018: DOI: https://doi.org/10.35654/ijnhs.v1i2.30 - Stepanus Maman Hermawan; Aurelia Citra Silalahi; Lydia Moji Lautan (International Journal of Nursing and Health Services (IJNHS), 2018)
Hipertensi adalah suatu kondisi di mana seseorang mengalami peningkatan tekanan darah di atas normal pada pemeriksaan tekanan darah. Berdasarkan kriteria JNC-VII yang diterapkan di Indonesia Hipertensi dinyatakan sebagai tekanan darah sama dengan atau lebih dari 140/90 mmHg. Penelitian ini bertujuan untuk mengidentifikasi faktor-faktor itukebanyakanmempengaruhi pasien kecemasan hipertensi di Rumah Sakit Umum M.Th. Djaman Sanggau. Penelitian ini merupakan penelitian kuantitatif dengan menggunakan metode penelitian deskriptif analisis denganCpendekatan. This study using purposive sampling involved 45 samples of hypertensive patients undergoing treatment at the hospital M.Th.Djaman Sanggau. Data analysis using Chi-Square. The result is there was no relationship between age and anxiety levels of hypertension patients p = 0.246 (p> 0.05), there was no relationship between sex with anxiety levels of hypertension patients p = 0.495 (p> 0.05), there was a relationship between the level of education and the level of anxiety of patients hypertension p = 0.011 (p <0.05). There is a relationship between work with the anxiety level of hypertension patients p = 0,000 (p <0,05). There is a significant relationship between the level of knowledge with the level of anxiety of patients with hypertension p = 0.001 (p <0.05). Anxiety is directly related to an increase in blood pressure so that someone needs to do counseling related to his condition to reduce anxiety, and need changes from individuals to change the risk factors for hypertension with healthy lifestyles such as fruit, vegetables, exercise regularly and reduce excessive consumption of calories and fat.